Perl in a nutshell - Patwardhan, Nate (In a nutshell (O'Reilly & Associates), 2002)
This complete guide to the Perl programming language ranges widely through the Perl programmer's universe, gathering together in a convenient form a wealth of information about Perl itself and its application to CGI scripts, XML processing, network programming, database interaction, and graphical user interfaces. The book is an ideal reference for experienced Perl programmers and beginners alike. With more than a million dedicated programmers, Perl is proving to be the best language for the latest trends in computing and business, including network programming and the ability to.